1988
DOI: 10.1161/01.hyp.11.6.635
|View full text |Cite
|
Sign up to set email alerts
|

Increased alpha-adrenergic receptor affinity in resistance vessels from hypertensive rats.

Abstract: SUMMARY a-Adrenergic receptor-related properties, specifically, norepinephrine affinity, occupancy and reserve during contraction, were determined in segments of rat resistance arteries. These were obtained from the superior mesenteric bed of spontaneously hypertensive rats and Wistar-Kyoto strain controls. Receptor affinity for norepinephrine in the spontaneously hypertensive rats was significantly greater than that for the Wistar-Kyoto controls. There were no differences in the estimates of receptor occupanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 23 publications
3
13
2
Order By: Relevance
“…While incubation with a COX inhibitor failed to restore -and in fact decreased -the vasodilator response to Ach of aortas from blueberry-fed SHR, in Phe-induced vasoconstriction, the suppression of vasoconstriction in SHR-BB aortas was greater, in comparison to SHR-C, when MFA was present. Even though there is functional evidence of α-adrenergic receptors in the vasculature of young SHRs, their effect is limited compared to aged SHRs [30,31]. In the current study, we support that there is no significant effect of our blueberry-enriched diet on the vessel sensitivity to the adrenoreceptor, unless NOS and COX enzyme synthesis is inhibited.…”
Section: Discussionsupporting
confidence: 66%
“…While incubation with a COX inhibitor failed to restore -and in fact decreased -the vasodilator response to Ach of aortas from blueberry-fed SHR, in Phe-induced vasoconstriction, the suppression of vasoconstriction in SHR-BB aortas was greater, in comparison to SHR-C, when MFA was present. Even though there is functional evidence of α-adrenergic receptors in the vasculature of young SHRs, their effect is limited compared to aged SHRs [30,31]. In the current study, we support that there is no significant effect of our blueberry-enriched diet on the vessel sensitivity to the adrenoreceptor, unless NOS and COX enzyme synthesis is inhibited.…”
Section: Discussionsupporting
confidence: 66%
“…As pointed out by Nyborg and Bevan [40], none of these results are necessarily at odds with the current study. They reported that mesenteric resistance arteries from spontaneously hypertensive rats are more sensitive to norepinephrine than those from NT rats.…”
Section: Discussioncontrasting
confidence: 88%
“…In the present study, the dissociation constant for norepinephrine in DOCA hypertensive rats (1.29xlO~7 M) is similar to that determined by Smith et al 4 in aldosterone hypertensive rats (4.8xlO~7 M) but is 10-fold less than the dissociation constant for the agonist in mesenteric arterioles from SHR (1.29xl(r 6 M). 10 Although we found no evidence of a change in agonist affinity, a decrease in receptor affinity for the ai-antagonist 125 I-(±) BE, the radiolabeled derivative of 2-[5(4hydroxy-phenyl)-ethyl aminomethyl] tetralone or HEAT, has been reported in mesenteric arteries from DOCA hypertensive rats. 1 This disparity may be related to methodological differences but also suggests that affinity may differ between agonists and antagonists, supporting postulated differences in receptor recognition sites for these two classes of compounds.…”
Section: Discussioncontrasting
confidence: 62%